2015
DOI: 10.4236/ojmm.2015.54024
|View full text |Cite
|
Sign up to set email alerts
|

Batumin—A Selective Inhibitor of Staphylococci—Reduces Biofilm Formation in Methicillin Resistant <i>Staphylococcus aureus</i>

Abstract: The antibiotic batumin, produced by Pseudomonas batumici, has been shown to be highly active against 123 type and reference strains and clinical isolates of 30 Staphylococcus species (including MRSA and small colony variants-(SSCVs) of S. aureus, S. epidermidis and S. haemolyticus). Batumin activity against these bacteria did not depend on the species, origin or resistance to other antibiotics and its MIC was 0.0625 -0.5 µg/ml. Batumin influence on biofilm formation was studied in clinical isolates of S. aureu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“… 6 , 7 Batumin has been patented in the Ukraine and formulated as Diastaf and used to detect staphylococci by taking advantage of its selectivity for these strains. 8 Decreased biofilm formation has also been reported for the majority of S. aureus strains investigated 9 and it has been found to reduce nasal S. aureus carriage. 10 Peschel and co-workers have recently highlighted the potential scope of narrow spectrum antibiotics in the control of bacterial populations.…”
Section: Introductionmentioning
confidence: 81%
“… 6 , 7 Batumin has been patented in the Ukraine and formulated as Diastaf and used to detect staphylococci by taking advantage of its selectivity for these strains. 8 Decreased biofilm formation has also been reported for the majority of S. aureus strains investigated 9 and it has been found to reduce nasal S. aureus carriage. 10 Peschel and co-workers have recently highlighted the potential scope of narrow spectrum antibiotics in the control of bacterial populations.…”
Section: Introductionmentioning
confidence: 81%
“…[15] In addition, it has been shown to efficiently disrupt and prevent the formation of S. aureus biofilms. [16] Despite its promising biological activity,n of urther clinical development has been pursued due to al ack of knowledge regarding its precise mechanism of action. Kalimantacin Ah as been proposed to inhibit FabI in S. aureus (saFabI) based on radiolabelled precursor incorporation studies as well as the presence of aF abV-like resistant isoform in the kalimantacin biosynthetic operon in P. fluorescens.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary clinical experiments with kalimantacin A, administered as a 0.1 % ointment, have indicated that it is highly effective in the treatment and control of nasal S. aureus infections . In addition, it has been shown to efficiently disrupt and prevent the formation of S. aureus biofilms . Despite its promising biological activity, no further clinical development has been pursued due to a lack of knowledge regarding its precise mechanism of action.…”
Section: Introductionmentioning
confidence: 99%
“…Still less is known about these properties of medically used antibiotics, in particular about batumin -polyketide antibiotic produced by Pseudomonas batumici -and its plant-interaction mechanisms. Batumin produced by a saprotrophic Pseudomonas strains has shown high and selective activity against staphylococci [6][7][8] which is several folds higher than against other test-microorganisms. During many years of intensive study, attention was focused upon biosynthesis of batumin, its chemical structure, perspectives of medical use, but its ecological and physiological role, function in producing strain, mechanism of antimicrobial action (in particular against soil bacteria) remained undiscovered.…”
mentioning
confidence: 99%